2022
DOI: 10.3389/fenrg.2021.778501
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Solar Geothermal Heat Pump System Model Demonstration Study

Abstract: In this paper, the development and demonstration of a hybrid solar geothermal heat pump polygeneration system is presented. The poly-generation system has been designed, modeled, and simulated in TRNSYS software environment. Its performance was assessed followed by installation and demonstration at a demo site in Cheongju, Korea. The space heating and cooling load of the building is 13.8 kW in heating mode at an ambient temperature of −10.3°C and 10.6 kW in cooling mode at an ambient temperature of 32.3°C. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Consequently, there is a need for comprehensive studies on the sensitivity of system performance to variations in operational control. The sensitivity study presented in this paper revealed the advanced system control logic [40].…”
Section: Introductionmentioning
confidence: 81%
“…Consequently, there is a need for comprehensive studies on the sensitivity of system performance to variations in operational control. The sensitivity study presented in this paper revealed the advanced system control logic [40].…”
Section: Introductionmentioning
confidence: 81%
“…As shown in Figure 19, with a targeted COP of 2, heat sources need to be adjusted depending on the process temperature. If the available waste heat does not allow to satisfy the design, it is also possible to design a hybrid system with solar thermal [50] or geothermal pits [169]. Alternative solutions to provide further efficient systems are to rework the heat pump design and sufficiently increase its exergy efficiency to enable good performances with greater temperature lift.…”
Section: Vapor Compression Heat Pumpsmentioning
confidence: 99%
“…The prolonged operation of a GHP system causes problems with the ground thermal environment due to ground heat accumulation because of this load imbalance, which reduces the performance of the system [13]. Hybrid GHP systems are considered an economical and practical alternative to compensate for these problems [14][15][16][17][18]. Hybrid GHP systems use a secondary heat sink for buildings with large cooling loads or a secondary heat source for buildings with large heating loads [19].…”
Section: Introductionmentioning
confidence: 99%